Analisis Kesalahan Penulisan Kata (Akhtho’ Imlaiyyah) pada tulisan mahasiswa Prodi PAI IAIN SAS Bangka Belitung - Ela Isnani Munawwaroh (Tarbawy : Jurnal Pendidikan Islam, 2020)
Tahsinul Kitabah is one of the compulsory courses for the students of the islamic education program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. At the last of the first semester, I found that the students had many difficulties in writing the Arabic language. Based on that, I wanted to identify the mistakes in the student’s writing. In Arabic science, the mistakes are called by akhtho’ imlaiyyah. For this research, I used a qualitative approach and a descriptive method. And for collecting the data, I used observation, documentation, and interview method. The result of this research is the mistakes of student’s of Islamic education program class A, B, C, and F for the first semester of 2019/2020 school year writing in Arabic is about hijaiyah writing, ta’ marbuthah and ta’ maftuhah, short and length of words, identification of the sound of hijaiyah letter, writing words that have tanwin and tasydid, stringing the letters, and alif lam syamsiah. That's all is be caused by the linguistic’s aspect and non linguistic’s aspects.